Neutrophil-to-Lymphocyte Ratio in Ovarian Cancer Patients with Low CA125 Concentration - Zhang, Hongyan (Biomed Res Int, 2019)
Ovarian cancer cases with low CA125 concentration are problematic and increase the high false negative results ratio during routine physical examination testing. Unfortunately, patients without early discovery have very low survival rates. In our study, we investigated the possible role of differential leukocyte counts and the neutrophil-to-lymphocyte ratio (NLR) in ovarian cancer patients to identify an additional discriminative marker to avoid missing diagnoses in normal physical examinations. One hundred seventy-three patients with epithelial ovarian cancer and 70 healthy controls were involved in our study. Based on the results, compared with the healthy controls, NLR was significantly different both in the low CA125 concentration group and in the complete patient group, indicating that NLR could be an effective marker for ovarian cancer screening. According to ROC, sensitivity, specificity, and NPV results, CA125 >35 U/ml is a good indicator for cancer in routine physical examination. However, in patients with low CA125 concentration, the CA125>7.65 U/ml and NLR >1.72 group yielded increased sensitivity with appropriate specificity and higher NPV results than the CA125 >35 U/ml group. We believe CA125>7.65 U/ml and NLR >1.72 should be effective makers for patients with low CA125 concentration. As a more sensitive and cost-effective strategy, this method could be conducted during routine ovarian cancer screening.